«Twelve points» by brigadier s. Velyaminov – the project of reforming the tax system and administrative apparatus of Hetman-rule in 1722 – 1727 - Безрук, Т. В. (Problems of legality, 2014)
The article examines the reasons for the preparation and content of position paper – «The Twelve points» by brigadier S. Velyaminov, that was found in Kharkiv archives and introduced to the scientific community in the 80-s of the XIX century by famous pre-revolutionary scholar A. Y. Yefymenko (1848 – 1918). It is shown that the orientation of the financial policy of the Russian government belonged to the more general problem of ukrainian-russian relations and the role of personal factor in it. The main purpose of the position paper by S. Velyaminov was, first, to reform the tax system of Hetman-rule and, secondly, to create transitional management model that would facilitate the incorporation of the Cossack-Hetman state to the Russian Empire.